Perkiraan Pertumbuhan Ekonomi Sektor Pertanian Dalam Pembangunan Ekonomi Di Kabupaten Lebong - As’ad As’ad (PARETO : Jurnal Ekonomi dan Kebijakan Publik, 2018)
By using trend analysis method, this study aims to find how much agricultural sector is needed to achieve economic growth in Lebong District for the next five years (2016-2021). The result shows that Agriculture Sector will increase from 766,8 million in 2016 to 907,506 million in the 2021.This research also analize the effect of agriculture sector to economic growth in Lebong. We used Simple Linear Regression analysis and we found that agriculture sector has positive significant effect on economic growth in Lebong.